2017
DOI: 10.1111/ctr.12978
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of compatible pair participants in kidney paired donation at a single center

Abstract: Compatible pairs of living kidney donors and their intended recipients can enter into kidney paired donation (KPD) and facilitate additional living donor kidney transplants (LDKTs). We examined 11 compatible pairs (the intended recipients and their intended, compatible donors) who participated in KPD, along with the recipients' 11 matched, exchange donors. The 11 pairs participated in 10 separate exchanges (3 were multi-center exchanges) that included 33 total LDKTs (22 additional LDKTs). All the intended dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…An important finding in this study is that the prospect of facilitating transplantation among additional patients in and of itself appears to be a strong motivator for TCs to consider KPD, and, in both surveys and interviews, was cited as the most important factor driving their desire to participate as a compatible pair. As in prior studies, 6,8,22,23 finding a "better match" or medical advantage for the intended TC was also cited by both PLDs and TCs as an important motivator for participating in KPD and has the potential to further increase willingness to participate as a compatible pair.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…An important finding in this study is that the prospect of facilitating transplantation among additional patients in and of itself appears to be a strong motivator for TCs to consider KPD, and, in both surveys and interviews, was cited as the most important factor driving their desire to participate as a compatible pair. As in prior studies, 6,8,22,23 finding a "better match" or medical advantage for the intended TC was also cited by both PLDs and TCs as an important motivator for participating in KPD and has the potential to further increase willingness to participate as a compatible pair.…”
Section: Discussionmentioning
confidence: 65%
“…4,5 In 2010, Ratner and colleagues first described the participation of 2 compatible pairs in a kidney chain and reported a certain ambivalence toward participating as a compatible pair in KPD. 6 In 2012, Bingaman et al 7 reported the participation of 17 compatible pairs in their kidney exchange programs, and, more recently, Weng et al 8 described the participation of 11 compatible pairs in their single-center KPD program.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies should also consider how paired exchange networks can ensure equipoise for all compatible pairs. While NKR is the largest single network for paired exchange, other networks have reported use of compatible pairs with varying measures of match quality 9,13,14 . Several investigators have suggested approaches to improve the ethical use of compatible pairs in paired exchange including a “reciprocity‐based strategy.” 23 Gill et al suggest prioritizing deceased donor allocation for paired exchange recipients who were originally part of a compatible pair; this would protect from graft failures over a 10‐year horizon.…”
Section: Discussionmentioning
confidence: 99%
“…Donor–recipient pairs that receive satisfaction in an altruistic act may seek biological equipoise. Other donor–recipient pairs may seek donors of younger age, larger nephron mass, fewer HLA mismatches, or general donor quality measured by the living donor kidney profile index (LKDPI) 13–17 …”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported the success of kidney transplantation across the blood group barrier (23,24), but the risks for severe infection, antibody-mediated rejection, and postoperative bleeding were all increased in an ABO-incompatible patient groups. Britta (27).…”
Section: Discussionmentioning
confidence: 99%